Intellectual Capital Analysis in Improving Profitability of Islamic Banking in Indonesia - Erwin Saputra Siregar; Mellya Embun Baining; Oktavia Sri Wardani (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
This research aims to test intellectual capital improvingthe profitability of Islamic banking in Indonesia from 2015 to 2019. The dependent variable in the study was the profitability of Islamic banking, consisting of Return on Asset (ROA). In contrast, the independent variable in the study was Intellectual Capital (VAIC), consisting ofValueAdded Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). This research emphasizes the importance of intellectual capital disclosure in financial statements to improve financial performance. The data used is Islamic bank data registered with the Financial Services Authorityfrom 2015to 2019. Intellectual Capital's measurement model uses Pulic Models, namely VAIC, VACA, STVA, and VAHU. Data is analyzed descriptively quantitatively with multiple linear regression analysis tools. The results showed thatVACA and STVA positively affect ROA in Islamic banks in Indonesia, and VAIC and VAHU have a significant adverse effect on ROA in Indonesia.